Soziale Arbeit in der Migrationsgesellschaft (Schriften der Katholischen Hochschule Nordrhein-Westfalen, 2013)
Migration has influenced and changed the society of the Federal Republic of Germany, its working and living environments, in many ways. What tasks, but also what opportunities are there for social work in a society shaped by immigration? The volume contains highly topical articles from an interdisciplinary perspective.